Syntaktisk komplexitet i inlärarsvenska: en jämförelse mellan finska universitets-studenters muntliga och skriftliga produktion på två olika färdighetsnivåer - Mäkilä Mari (Finland, 2022)
This study examines how proficiency level affects syntactic complexity in written and spoken L2 Swedish. Spoken production can be more challenging for learners at lower proficiency levels due to the limited resources for processing the target language (Skehan 1998), whereas the possibility for more extensive planning during the writing process enables the production of syntactically complex structures in writing (Skehan & Foster 2012, Tavakoli 2014). Automaticity at higher proficiency levels reduces the cognitive load that the spoken production imposes on learners and facilitates the production of complex structures in speech (Leonard & Shea 2017). However, few studies have directly compared complexity in written and spoken L2 production, and earlier studies have resulted in contradictory results (Kuiken & Vedder 2012b:364–365). The data in this study consist of monologues and essays produced by 31 Finnish university students. Some subjects study Scandinavian languages as their major, while others take part in a Swedish course at the Centre for Language and Communication Studies. The analysis is based on surface-level complexity measures, such as the mean length of production units and the dependent clause ratio. The results show that proficiency plays an important role especially in spoken production and, therefore, also in the differences between written and spoken production. At the lower proficiency level, written production is significantly more complex when it comes to the mean length of T- and AS-units, the dependent clause ratio, and the ratio of dependent clauses with a sentence adverbial. Surprisingly, the mean clause length shows higher complexity in speech at the lower proficiency level. At the higher proficiency level, there are no statistically significant differences between the modalities. These results indicate that the cognitively more demanding task of producing L2 speech can lead to the use of simple structures at the lower proficiency level, resulting in a greater difference between written and spoken complexity. The learners at the higher proficiency level seem to be able to produce complex structures also in the spoken mode, and therefore, there are no significant differences between written and spoken complexity at this level.